Substance use and associated diseases among injured persons (Health Renaissance, 2012)
Introduction: Alcohol use and alcohol use disorders are associated with increased risks of mortality and morbidity from injury and violence. Chronic health conditions are taken as risk factors for injury as well as the consequences of the injury. Very few studies have noted about diseases among injured person. Objectives: To find out the use of alcohol among injured persons and to explore the associated diseases among injured persons. Methods: In this study 10% of the households of Dharan i.e. 1398 household were selected as the sample size. A systematic random sampling was used to select the 10% household from each ward. A pre-tested questionnaire was used to collect demographic information and information related to injuries to the persons suffered from injuries, alcohol intake prior to injury and whether they suffered from any chronic diseases or not. Results: Among 299 injured persons, 20.4% of them used to take alcohol. It was noted that 5.4% consumed alcohol prior to the injury. About 8 % injured persons were hypertensive and 7.7% of them suffered from visual problem. About 10 % of the major injured persons were suffering from physical disability. Conclusion: Consumption of alcohol, chronic health problems like hypertension, visual impairment and physical disability are common among the injured persons. DOI: http://dx.doi.org/10.3126/hren.v10i3.7136 Health Renaissance; September-December 2012; Vol 10 (No.3);203-207